2010
DOI: 10.3233/ch-2010-1343
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glycogen synthase kinase-3β prevents activation of focal adhesion kinase after ischemia/reperfusion of the rat lung

Abstract: Recent studies on the mechanisms of ischemic preconditioning in myocardial tissue have presented convincing evidence that multiple protective pathways converge on inhibition of glycogen synthase kinase-3␤ (GSK-3␤). To directly address the role of GSK-3␤ in ischemia and reperfusion (I/R) of the lung, a rat model of left lung in situ ischemia was used. The specific non-competitive inhibitor of GSK-3␤, TDZD-8, was injected (3 mg/kg, vehicle in controls) 5 min before the left lung hilum was occluded for 60 min. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Our bioinformatics analysis results suggested that GSK3β was a hub gene which may be regulated by miR-144. GSK3β has been reported to aggravate lung I/R injury while inhibiting GSK3β mends lung function following I/R injury (Waldow et al 2010). It has been reported that GSK3β is a pro-inflammatory agent, and that inhibiting the expression of GSK3β inhibits the inflammatory response and can be achieved by inhibiting autophagy to suppress NLRP3 inflammasome activation, therefore alleviating cerebral I/R injury in rats (Tantray et al 2017;Wang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our bioinformatics analysis results suggested that GSK3β was a hub gene which may be regulated by miR-144. GSK3β has been reported to aggravate lung I/R injury while inhibiting GSK3β mends lung function following I/R injury (Waldow et al 2010). It has been reported that GSK3β is a pro-inflammatory agent, and that inhibiting the expression of GSK3β inhibits the inflammatory response and can be achieved by inhibiting autophagy to suppress NLRP3 inflammasome activation, therefore alleviating cerebral I/R injury in rats (Tantray et al 2017;Wang et al 2019).…”
Section: Discussionmentioning
confidence: 99%